2021
DOI: 10.1177/11297298211006972
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistula cannulation in hemodialysis: A vascular access clinical practice guidelines narrative review

Abstract: The cannulation of an arteriovenous fistula (AVF) by the hemodialysis (HD) nurse is challenging. Despite it being the focus of extensive research, it is still one of the majors causes of damage making it prone to failure. A considerable number of Clinical Practice Guidelines (CPGs) for the management of vascular access (VA) have been published worldwide over the past two decades. This review aimed to assess all information available in the selected CPG regarding AVF cannulation for HD providing a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Arteriovenous access cannulation should not be restricted to the technique, as other aspects are very important for its success. Several aspects influence the quality of access cannulation and may thus affect access survival and the quality of dialysis [15]. Identification of access flow, selection of cannulation site, selection of needles type, and preparation of cannulation site, are very important before arteriovenous access cannulation.…”
Section: Optimizing Cannulationmentioning
confidence: 99%
“…Arteriovenous access cannulation should not be restricted to the technique, as other aspects are very important for its success. Several aspects influence the quality of access cannulation and may thus affect access survival and the quality of dialysis [15]. Identification of access flow, selection of cannulation site, selection of needles type, and preparation of cannulation site, are very important before arteriovenous access cannulation.…”
Section: Optimizing Cannulationmentioning
confidence: 99%
“…Only with solid knowledge of vascular access can nurses provide proper nursing and instructions to HD patients and promptly identify vascular access-related complications, which will help patients to improve their capabilities in maintaining vascular access and thus prolong the patency of vascular access. Studies (12,13) have shown that the training of HD unit nurses on vascular access has a positive impact on the quality management of vascular access by improving the AVF puncture techniques, reducing vascular access complications (e.g., thrombosis and stenosis), and prolonging the patency of vascular access. Therefore, hospital managers should strengthen the training and assessment of HD unit nurses' knowledge of vascular access, especially in terms of vascular access assessments, AVF puncture techniques, and other practical skills.…”
Section: Knowledge Of Vascular Access Among Hd Unit Nurses Needs To B...mentioning
confidence: 99%
“…Naturally, HD unit nurses with more working years are exposed to more HD patients with vascular access-related nursing problems than those with fewer working years, and also have more work experience. For example, AVF cannulation is managed with graded authorization based on working years, and the cannulation of new and difficult AVFs is mainly performed by nurses with more working years (13). Therefore, HD unit nurses have more knowledge of vascular access.…”
Section: Years Of Service Affects the Knowledge Of Vascular Access Am...mentioning
confidence: 99%
“…This may be associated with the factor that the vascular access outcome is a result of the complex interplay of several risk factors, and patients on HD have heterogeneous characteristics. Vascular access outcomes are known to be influenced by various factors, including demographic factors such as age, sex, race/ethnicity; clinical comorbidities like cardiac, pulmonary, or peripheral vascular diseases, diabetes, obesity; as well as technical factors like surgical experience, vascular access care, intervention methods, needling practices, and post-needling care [19][20][21]. Vascular access-related outcomes of patients on HD are influenced not only by simple baseline characteristics and comorbidities but also by factors such as the vascular status, vascular access location or AVG presence, the specific HD center, and the experience of the nursing staff.…”
mentioning
confidence: 99%